A STANDARD OPERATING PROCEDURE VIDEO FOR DAUNI SPA AND BEAUTY HOUSE TO STANDARDIZE ITS THERAPISTS’ SERVICE QUALITIES - Debry Yusi Sandria; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2017)
Dauni Spa, the company where I did my internship, provides spa treatment, sauna, and salon service. During my internship at Dauni Spa, I found there are various practices of massage techniques performed by the therapists that lead to inconsistency in the service qualities. This problem certainly resulted in unsatisfactory treatment because the customers would not be satisfied to receive inconsistent service quality. Aside from this problem, many newly-recruited therapists did not know the standard procedures of massage in Dauni Spa while they needed to start working very soon. Therefore, I intend to make a standard operating procedure (SOP) video as a solution to the problems. For the newly recruited therapists, the SOP video can give effective and efficient instructions of the standard procedures in Dauni Spa. For the old therapists, this video works as a standard service quality that should be put into practice by all therapists. The basic content of this video is the procedures of the massage and a little background information about Dauni Spa. From this video, there are some benefits that Dauni Spa can get. It can complete the written SOP that they have, cut down the cost of a trainer, and bring a good impact to the customers’ satisfaction.